2021
DOI: 10.5761/atcs.oa.19-00293
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Sternal Wound Infections in Women Using an External Sternum Fixation Corset

Abstract: Purpose: Deep sternal wound infection (DSWI) and mediastinitis are devastating complications after median sternotomy. Previous studies demonstrated an effective prevention of sternal wound infection (SWI) using an external sternal corset in high-risk cardiac surgery patients. The aim of this study is to assess the preventive effect of the Stern-E-Fix corset in high-risk poststernotomy female patients. Methods: A total of 145 high-risk female patients undergoing cardiac surgery through median sternotomy were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…A previous descriptive systematic review concluded that early post-sternotomy use of an external non-elastic sternal support device would reduce overall sternal wound complications and may reduce the hospital LOS [ 10 ]. In this context, observational series showed also similar findings as the current analysis [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…A previous descriptive systematic review concluded that early post-sternotomy use of an external non-elastic sternal support device would reduce overall sternal wound complications and may reduce the hospital LOS [ 10 ]. In this context, observational series showed also similar findings as the current analysis [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…Sternal instability “per se” increases the risk of DSWI, whereby external stabilisation reduced the rate of DSWI in a large randomised trial regardless of conventional factors including age, female gender, DM, higher BMI, COPD, renal failure, the logistic EuroSCORE and non-elective indication for surgery [ 43 ]. A recent study in high-risk female patients undergoing cardiac surgery [ 44 ] demonstrated reduced DSWI when using a postoperative external stabilisation corset [ 45 ]. Conversely, intense coughing after surgery alone or in combination with, underestimated pleural effusions are factors promoting sternal instability [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gender-related factors that simplify the bacterial penetration of the wound or reduce immune response are of interest in the current literature [16]. Sex-specific reports of outcomes after cardiac surgery have been controversially discussed [17,18].…”
Section: Discussionmentioning
confidence: 99%